EFFECT OF AGE OF THE SHEA TREE (VITELLARIA PARADOXA) ON THE FLOW OF SHEA LATEX - Quainoo, A. K.; Dugbatey, J. G (UDS International Journal of Development, 2016)
Shea latex samples was tapped from ten experimental trees in five age groups (0-3 years (T3), 4-6 years (T6), 7-9 years (T9), 10-12 years (T12) and 13-15 years (T15)) each obtained from Nyankpala in the Tolon – Kumbungu District in Northern Ghana. The trees were identified randomly and tagged for latex extraction from February to April 2016. Results indicated that shea latex flow decreases with the age of the tree. The mean shea latex flow obtained over the period were 37.55g, 32.54g, 23.89g, 15.38g and 9.00g for T3, T6, T9, T12 and T15 respectively. The proximate composition of the Shea latex with respect to the various ages of the Shea trees also revealed a significant variation. Crude fat and moisture were slightly higher in the younger trees than the mature trees. However, crude protein, crude fibre, ash and carbohydrate were found to be significantly higher in the mature trees. Key words: Shea latex, Proximate composition, Crude fat, Crude protein, Crude fibre, Moisture content, Ash content, Carbohydrat